ANALISIS PENGARUH PENDIDIKAN, PENGANGGURAN, DAN PDRB PER KAPITA TERHADAP PENGENTASAN KEMISKINAN PROVINSI LAMPUNG 2020-2024 - Ramadanti, Sandrina; Purnama, Dimas Aji; Farhandhanu, Fazle Mawla; Syafitri, Nabilla Echa Sheila; Sabila, Resya (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the influence of education, unemployment, and Gross Regional Domestic Product (GRDP) per capita on poverty levels in Lampung Province during the 2020–2024 period. Poverty issues in Lampung continue to exhibit considerable disparities across regions, making the use of panel data relevant for capturing spatial and temporal variations. The study employs a quantitative approach with panel data regression analysis. Model selection was conducted using the Chow Test, Hausman Test, and Lagrange Multiplier Test, resulting in the Random Effect Model as the most appropriate. The findings indicate that GRDP per capita has a negative and significant effect on poverty. Education shows a negative but insignificant effect, while unemployment also exhibits a negative and insignificant effect on poverty levels. Simultaneously, all three variables significantly influence poverty in Lampung Province. The Adjusted R² value of 0.657 indicates that 65.7% of the variation in poverty can be explained by the model, while the remaining portion is influenced by factors outside the model. These results highlight the importance of inclusive economic growth and equitable access to education in supporting poverty reduction efforts in Lampung Province.